Polyoxovanadates with emerging biomedical activities - Aureliano, Manuel (2021)
Polyoxovanadates (POVs) are a subclass of a larger family of polyanionic group V and VI metal-oxo clus ters that are known as polyoxometalates (POMs). POMs have been found to have antidiabetic, antibacte rial, antiprotozoal, antiviral and anticancer activities, which have sparked interest in their use as bioinorganic drugs. Among POVs, decavanadate ([V10O28] 6 ; V10) is an isopolyoxovanadate recently described to have several medicinal applications. In the present review, recent insights into POVs with emergent anticancer, antimicrobial and antiviral applications are described. Additionally, POVs’ stability and speciation under experimental biological conditions as well as POVs (in particular, V10) in vivo and ex vivo effects are highlighted. Finally, we report the most important 21st century studies of POVs’ effects and/or targets against cancer, bacteria and viruses including: apoptosis, cell cycle arrest, interference with ions transport system, inhibition of mRNA synthesis, cell morphology changes, changes in metabolic pathways, phosphorylase enzyme inhibition and cell signaling, formation of reactive oxygen species, lipid peroxidation, inhibition of viral mRNA polymerase, inhibition of virus binding to the host cell, penetra tion and interaction with virus protein cages.